An analysis of Philippine income tax reforms - Mendoza, Ronald U (Archīum Ateneo, 2015)
Ensuring a progressive tax structure while observing economic growth objectives has been one of the significant challenges in taxation policy. A progressive tax structure would mean that those with the lower ability to pay will face a relatively lower tax burden, imposing much higher tax rates to those with a higher ability to pay. But this could have the effect of discouraging work for the relatively more productive taxpayers hence a trade-off between increased revenues and a more equitable tax system. Various income tax reform proposals has recently been filed in the Philippine legislature, all with the aim of updating the 1997 income tax structure, and ensuring a more progressive income tax system while still mindful of growth objectives. This paper analyzes the three income tax reform proposals filed by Senator Juan Edgardo M. Angara (Senate Bill 2149), Senator Paolo Benigno A. Aquino IV (Senate Bill 1942), and Senator Ralph G. Recto (Senate Bill 716). Using data from the Bureau of Internal Revenue and the 2012 Family Income and Expenditure Survey (FIES), this paper focuses on the possible implications of the three income tax reform proposals on progressivity and economic growth through revenue generation. This paper will stop short of providing suggestions on what could be an optimal tax structure for the Philippines. It will also provide some of the key policy issues relevant to tax progressivity and how this could affect inclusive growth and development.